Analysis of Teachers’ Perceptions on the Implementation of Ki Hajar Dewantara’s Educational Philosophy in the Independent Learning Curriculum - Hermawan, Andi; Rocha, Thiago; Lima, Rafaela (International Journal of Educational Narratives, 2025)
Background. This study explores teachers’ perceptions of the implementation of Ki Hajar Dewantara’s educational philosophy within the framework of the Independent Learning Curriculum. As Indonesia shifts toward a more student-centered educational model, rooted in the values of independence, critical thinking, and creativity, understanding teachers’ perspectives on integrating Dewantara’s philosophy is crucial. Purpose. Dewantara’s philosophy, which emphasizes freedom of learning and the development of students’ full potential, offers a valuable foundation for the Independent Learning Curriculum introduced by the Indonesian Ministry of Education. Method. The aim of this research is to analyze teachers’ views on how effectively the principles of Dewantara’s educational philosophy are being integrated into the curriculum, and the challenges and benefits they perceive in this process. A qualitative approach was used, involving in-depth interviews with 20 primary and secondary school teachers across various regions. Results. The findings reveal that while teachers generally appreciate Dewantara’s educational philosophy, they face challenges such as limited resources and insufficient professional development opportunities. However, they also recognize the positive impact of his principles in fostering a more holistic approach to education. Conclusion. The study concludes that there is a need for more structured support and resources for teachers to fully implement Dewantara’s philosophy within the Independent Learning Curriculum.